تأثير العائد والمخاطر في بيئة المنظمة دراسة استطلاعية لأراء عينة من العاملين (مجلة المنصور, 2025)
the relationship between return and risk is one of the most important elements that an organization should consider while making investment or planning decisions. In a changing business environment, achieving future returns is the primary goal of any organization, while controlling potential risks is the main challenge. Levels of return and risk vary from organization to organization and depend on the nature of the industry and the needs of the individual organization. The questionnaire